Saturation recovery allows T1 mapping in the human heart at 7T with a commercial MRI scanner - Rodgers, C; Tao, Y; Piechnik, S; Liu, A; Francis, J; Neubauer, S; Robson, M (BioMed Central, 2015)
Myocardial T1 mapping at 1.5T and 3T distinguishes powerfully between normal and diseased tissue with focal and diffuse pathology. We recently reported the first human myocardial T1s at 7T using the ShMOLLI+IE inversion recovery sequence. Yet even using a unique 7T scanner with 16kW RF output, perfect magnetization inversion was impossible. We now introduce a saturation recovery method to enable myocardial T1 mapping with standard commercial 7T MRI scanners.